2010
DOI: 10.1017/s0022112009993430
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale structures in turbulent and reverse-transitional sink flow boundary layers

Abstract: Aspects of large-scale organized structures in sink flow turbulent and reverse-transitional boundary layers are studied experimentally using hot-wire anemometry. Each of the present sink flow boundary layers is in a state of ‘perfect equilibrium’ or ‘exact self-preservation’ in the sense of Townsend (The Structure of Turbulent Shear Flow, 1st and 2nd edns, 1956, 1976, Cambridge University Press) and Rotta (Progr. Aeronaut. Sci., vol. 2, 1962, pp. 1–220) and conforms to the notion of ‘pure wall-flow’ (Coles,J. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
20
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 47 publications
5
20
2
Order By: Relevance
“…Consequently, the outer layer frequently consists of extended regions of low turbulence. The shallow inclinations are in line with previous studies (e.g Piomelli et al 2000;Dixit & Ramesh 2010). and, as discussed later, are predominantly caused by the larger ∂U/∂y and ∂U/∂x relative to the vortex self-induction.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Consequently, the outer layer frequently consists of extended regions of low turbulence. The shallow inclinations are in line with previous studies (e.g Piomelli et al 2000;Dixit & Ramesh 2010). and, as discussed later, are predominantly caused by the larger ∂U/∂y and ∂U/∂x relative to the vortex self-induction.…”
supporting
confidence: 91%
“…The vortical structures extend to smaller distances away from the wall and their inclination angles decrease. Jang, Sung & Krogstad (2011) use DNS to reveal that the streamwise velocity correlation contours are aligned at shallower angles with the wall, while measurements of Dixit & Ramesh (2010) show that these inclination angles decrease systematically as K increases. For very mild FPG (K ∼ 0.08 × 10 −6 ), Harun et al (2013) find that the outer-layer large-scale structures are weaker than those in ZPG boundary layers.…”
Section: Introductionmentioning
confidence: 99%
“…The sink flow is the simplest accelerating boundary layer and has been studied numerically 24 and experimentally; [31][32][33][34] in this type of flows, K and the Reynolds number remain constant, resulting in statistical similarity in the flow direction. Therefore, a sink flow is substantially less expensive computationally, compared to spatially developing accelerating flows.…”
Section: Introductionmentioning
confidence: 99%
“…Hutchins et al [22,23] used two-point span-wise correlation to obtain statistical information regarding the width and spacing of the coherent structures. In literature, a number of studies can be found in which two-point correlation is used to obtain the shape of the structures inside the wake region [24,25].…”
Section: Introductionmentioning
confidence: 99%